2011
DOI: 10.1021/jp109082g
|View full text |Cite
|
Sign up to set email alerts
|

Study of the TiO to Anatase Transformation by Thermal Oxidation of Ti Film in Air

Abstract: The TiO to anatase phase transformation has been studied by transmission electron microscopy in this Article. It is shown that prior formation of TiO from Ti film can induce the formation of anatase by thermal oxidation in air; otherwise only rutile is formed. Ti film deposited on the NaCl (001) surface is induced to form epitaxial TiO film by thermal oxidation in air. Further thermal oxidation in air partially transformed TiO into anatase (A) with a parallel orientation relationship of {200}A//{200}TiO. Detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…This result is consistent with the previous results that TiO can lead to the formation of anatase [1,5,6]. In the previous cases of oxidation of TiO film [1] and anodized TiO film [6] the parallel orientation relationship of {100} TiO //{100} anatase between TiO and anatase was observed because epitaxial TiO films were used so that the TiO and anatase interfaces could be located. However, in the present case of randomly oriented TiO nanocrystals, the orientation relationship could not be observed.…”
Section: Tem Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…This result is consistent with the previous results that TiO can lead to the formation of anatase [1,5,6]. In the previous cases of oxidation of TiO film [1] and anodized TiO film [6] the parallel orientation relationship of {100} TiO //{100} anatase between TiO and anatase was observed because epitaxial TiO films were used so that the TiO and anatase interfaces could be located. However, in the present case of randomly oriented TiO nanocrystals, the orientation relationship could not be observed.…”
Section: Tem Analysissupporting
confidence: 92%
“…Further annealing at higher temperature in air turned the TiO into anatase with a parallel orientation relationship of {100} TiO //{100} anatase . That TiO can lead to the formation of anatase was attributed to the close similarity between their structures [1]. Other reports also confirmed that if TiO was formed first in vacuum deposition processes then anatase could be formed by subsequent thermal oxidation [2][3][4].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In any case, anatase may be stabilized by Ti 2+ in view of the TiO to anatase transformation by thermal oxidation of Ti film in air under the influence of NaCl template. 7 The 2 × 110 superstructure of rutile 44 45 The (Ti 3+ , Ti 2+ , H + )-codopant may also reside on the surface sites of TiO 2 nanocrystals for surface disordering, color change and band gap lowering. In fact, the disorderengineered darkish nanophase TiO 2 with narrowed band gap has been prepared by static aqueous solution from other precursor material to consist of two phases, i.e., a crystalline (anatase) TiO 2 quantum dot or nanocrystal as a core, and a highly disordered surface layer where dopants are introduced.…”
Section: Defect Chemistry and Bimodal Bandmentioning
confidence: 99%
“…Shabalin et al [42] presented an oxidation model of TiC, in which incorporation of carbon in TiO 2 stabilized the anatase phase. Meanwhile, Kao et al [44] observed the reversible transformation between TiO having an NaCl-type structure and anatase. They pointed out the similarity between their structures: TiC and TiN exhibit NaCl type structure with a lattice constant close to TiO; the anatase formation on TiC and TiN in thermal oxidation would be related to this NaCl-type structure.…”
Section: Tio 2 Layers On Ti and Ti Alloys For Biomedical Applicationsmentioning
confidence: 99%